Can intelligent virtual assistants improve cognitive function in older adults? A two-wave mediation study - Tianxin Cai; Shilong Ma; Renyao Zhong (Digital Health)
Objectives This study aims to investigate whether social networks and physical exercise mediate the relationship between new and constant use of intelligent virtual assistants (IVAs) and cognitive function in older adults in China and explore the potential differences across living arrangements and education levels. Methods This study utilized nationally representative longitudinal data from 2018 to 2020, including a sample of 8343 older adults aged 60–80. A path-analytic model was employed to examine the relationship between IVAs use and cognitive function, as well as the mediating roles of social networks and physical exercise. Results Constant and new IVAs use significantly affected cognitive function, mediated by social networks and physical exercise. For older adults living alone, both types of IVAs use had positive direct and indirect effects. Those living with children benefited mainly from new IVAs use, with indirect effects through physical exercise. Among less educated older adults, only new IVAs use showed significant effects through social networks. For those with higher education, both constant and new IVAs use positively impacted cognitive function directly and indirectly. Conclusions The use of IVAs can significantly improve cognitive function in older adults, with social networks and physical exercise being important mediating pathways. Policy suggestions were provided based on these results.